Consórcios com plantas de cobertura em sistema de rotação influenciam os atributos físicos do solo e a produtividade da soja - Rigotti, Adriel Rafael (2021)
In recent years, the domination of the Amazon biome by agricultural production systems has been observed, a fact that has caused significant changes in the chemical and physical attributes of the soil. Thus, alternatives such as rotation systems or the use of cover crops may be interesting strategies to improve the quality of this soil. The objective of this work was to verify and characterize the changes in soil physical attributes and soybean production parameters, after the cultivation of cover crops intercropped with Urochloa brizantha, compared to soybean succession followed by cotton. In addition, the aim was to identify the best combination of cover crops for structuring the porosity and water availability of the soil in the production system. To this end, an experiment was conducted in the municipality of Sinop-MT, evaluating the physical attributes of the soil and production parameters of the soybean crop, subjected to eight different treatments, seven of which were soybean production followed by the implementation of integrated production systems with consortia of cover crops (Super N, Caupi, Sunflower, Turnip, Crotalaria, and Sextuple), and one treatment represented by the soy/cotton succession. Undisturbed soil samples were collected in the 0-0.10 and 0.10-0.20 m layers for the determination of their attributes during three harvests (2017/18, 2018/19, and 2019/20). The attributes determined in the different treatments were: soil porosity, soil density, water retention curve, S index, optimal hydric interval, and penetration resistance. The integrated production systems provide modifications in soil properties in both layers evaluated. Among the systems evaluated, the management with direct sowing in soybean/cotton succession had the lowest soybean productivity values. The adoption of intercropping systems with cover crops contributed to the maintenance of the physical quality of the soil in agricultural areas of the Amazon biome, minimizing the adverse impacts of soil cultivation associated with the use of crop succession. Among the consortia studied, the Caupi, Turnip and Sextuple treatment presented better soil attributes and higher soybean yield values.